PENGARUH JUMLAH WISATAWAN TERHADAP TINGKAT HUNIAN KAMAR HOTEL DAN PENERIMAAN PAJAK HOTEL DI KOTA PONTIANAK - B01110026, GUNDA RANDA (Jurnal Pembangunan dan Pemerataan, 2016)
Most basic problem in hotels in the City Pontianak located on the number of tourists and occupancy rate hotel room. The imbalance between the increasing number of foreign tourists with occupancy rate hotel room will have an impact on tax revenues hotels and other economic sector. Research aims to understand how influence and analyze the number of tourists and occupancy rate hotel room for tax revenues hotel in The City Pontianak. This research in a description quantitative linear with an analysis of multiple regression with the help of computer program eviews. For research purposes used secondary data of time series 2009-2013 year. Data is collected from statistics ( BPS ) , journal , books and other research. Testing covering the statistics the determination ( R2 ) , the F and test t and classical the assumption that includes multikolinieritas , Autokorelasi And Heterokedastisitas. Observation data about 60 on 12 months 5 years during the period 2009 until 2013 in the City Pontianak . The result of this research suggests that the number of Domestic Tourists and foreign tourists influential positive and signinifikan against Occupancy Rate Hotel Room The City Pontianak, Occupancy Rate Hotel Room influential positive and significantly To Tax Revenues Hotel in the City Pontianak. Keywords: The Hotel , Domestic Tourists, Foreign Tourists , Occupancy